Toward an Epigenetic View of Our Musical Mind - Brigati, Claudio; Saccuman, Maria Cristina; banelli, barbara; divinci, angela; casciano, ida; Borzì, Luana; Forlani, Alessandra; Allemanni, Giorgio; Romani, Massimo (Frontiers in Genetics, 2012)
In our everyday life, we feel responsible for ourselves. Step by step, a premise is followed by action followed by consequences. This succession of events, seemingly dominated by the principle of cause and effect, is constantly scrutinized by our consciousness and makes us aware of the world. Even in the field of our more abstract behavior, such as practicing Art or Science, creation becomes our license of free individuals, finally liberating mankind from the instincts that dominate the animal world. But is this true? Recent studies seem to throw shadows of these certainties; here we review a series of data and introduce novel speculations on possible epigenetic mechanisms in our brain that could dictate how we perceive and perform creation, art and music in particular.